2013
DOI: 10.1016/j.physa.2012.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Scaling, stability and distribution of the high-frequency returns of the Ibex35 index

Abstract: Abstract. In this paper we perform a statistical analysis of the high-frequency returns of the Ibex35 Madrid stock exchange index. We find that its probability distribution seems to be stable over different time scales, a stylized fact observed in many different financial time series. However, an in-depth analysis of the data using maximum likelihood estimation and different goodness-of-fit tests rejects the Lévy-stable law as a plausible underlying probabilistic model. The analysis shows that the Normal Inver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
(58 reference statements)
0
11
0
3
Order By: Relevance
“…Other studies have also shown this distribution's superior empirical fit to other asset classes [54,39,26,27]. Using IBEX35 data, [60] find that the Normal Inverse Gaussian distribution provides an overall fit for the data better than any of the other subclasses of Generalized Hyperbolic distributions and much better than the Lévy-stable laws. More recently, Rachev et al [55] have deployed the NIG distribution, together with other statistical machinery, to study and (in their words) resolve such well-known 'puzzles' as (i) Predictability of asset returns (ii) The Equity Premium, and (iii) The Volatility Puzzle.…”
Section: Nig-type Distributionmentioning
confidence: 69%
“…Other studies have also shown this distribution's superior empirical fit to other asset classes [54,39,26,27]. Using IBEX35 data, [60] find that the Normal Inverse Gaussian distribution provides an overall fit for the data better than any of the other subclasses of Generalized Hyperbolic distributions and much better than the Lévy-stable laws. More recently, Rachev et al [55] have deployed the NIG distribution, together with other statistical machinery, to study and (in their words) resolve such well-known 'puzzles' as (i) Predictability of asset returns (ii) The Equity Premium, and (iii) The Volatility Puzzle.…”
Section: Nig-type Distributionmentioning
confidence: 69%
“…It seems reasonable to set it as the benchmark. Many studies, however, highlight the limited power of the normal distribution to describe financial data dynamics [13,14,17], and propose many alternatives such as the NIG or the skewed t, which are also compared to the normal.…”
Section: The Benchmark and Goodness-of-fitmentioning
confidence: 99%
“…We estimate the models via maximum likelihood as suggested by Suárez-García and Gómez-Ullate [14] and Clauset et al [22], and compare them using the Kolmogorov-Smirnov (K-S) test, the Anderson-Darling (A-D) test, and the Bayesian information criterion per observation (BIC o ). 2 The lower the value of any criterion, the better the fit [23].…”
Section: The Benchmark and Goodness-of-fitmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis shows that the kinematics and dynamics of the fluctuation of return and price in stock markets cover physics, biology, and nonlinear science, vibration theory, sociology, economics and human psychology, etc. [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%